Pembekuan Semen Ayam Kampung Menggunakan Pengencer yang Diperkaya dengan Berbagai Konsentrasi dan Jenis Gula - Khaeruddin, Khaeruddin; Kurniawan, Muhammad Erik (Jurnal Veteriner, 2020)
The aim of this study was to determine the type and concentration of sugar that was most suitable for use in semen extenders in freezing kampung rooster spermatozoa. Semen was collected from five roosters using massage method.  Immediately after collection, the semen was evaluated macroscopically and microscopically.  Semen was divided into twelve tubes.  Each of them diluted with ringer lactate egg yolk added with various sugar such as glucose, trehalose, sucrose and lactose combined with sugar concentration of 20 mM, 50 mM and 80 mM.  Liquid semen was packaged in a mini straw and was equilibrated, semen was frozen above the surface of the liquid nitrogen then it was stored in a container for 24 hours. Spermatozoa motility was evaluated after dilution, equilibration and thawing.  The results showed that there were no significant differences in quality (P> 0.05) with the treatment of various types of sugars, but there were significant differences in motility (P <0.05) with differences in sugar concentrations.  The best motility of spermatozoa was obtained at 50 mM and 80 mM sugar concentrations.  Spermatozoa motility after thawing was 36.56-37.19% with a sugar concentration of 50 mM and 80 mM, whereas a sugar concentration of 20 mM was only resulting 34.06% of motility.  The conclusion of this research is glucose, trehalose, sucrose and lactose can be added to the kampung rooster semen extender with a concentration of 50 mM for freezing.